Disorders of Sex Development: A Review of Medical and Psychosocial Aspects - Saktini, Fanti; Asikin, Hang Gunawan; Sarjana A.S, Widodo; Utari, Agustini (Diponegoro International Medical Journal, 2024)
Background: Disorders of Sex Development (DSD) refer to a spectrum of congenital conditions involving atypical chromosomal, gonadal, or phenotypic development. Although recent studies have improved our understanding of the medical management of DSD, the psychosocial impact and the role of multidisciplinary care in addressing these challenges remain less well known.Objective: This review aims to examine the classification, diagnostic approaches, and medical and psychosocial challenges associated with DSD, while also highlighting the importance of multidisciplinary support.Methods: A narrative review was conducted to explore the current research and clinical guidelines on DSD, including studies on medical management and psychosocial interventions.Results: The review found that early diagnosis and management are essential to reducing life-threatening risks and psychosocial distress in individuals with DSD. The impact of societal stigma, gender identity complexities, and increased rates of anxiety and depression were observed to contribute to body image concerns. A multidisciplinary care team, involving psychiatrists, endocrinologists, and other specialists, was highlighted as critical for holistic patient care.Conclusion: The findings underscore the importance of a multidisciplinary approach in addressing both the medical and psychosocial aspects of DSD. While collaborative decision-making and individualized care strategies showed positive outcomes, further research is needed to optimize long-term health and quality of life for individuals with DSD.